LEGAL ANALYSIS OF PRO BONO LEGAL AID IN FULFILLING THE RIGHTS OF MARGINALIZED GROUPS IN CIVIL LITIGATION: ANALISIS HUKUM TENTANG BANTUAN HUKUM PRO BONO DALAM MEWUJUDKAN HAK-HAK KELOMPOK MARGINAL DALAM PERKARA PERDATA - Nandhyra Syafa Nur Aisyah (ADHAPER: Jurnal Hukum Acara Perdata, 2026)
Access to justice for marginalized groups remains a major challenge in civil litigation in Indonesia. High litigation costs, limited legal literacy, uneven distribution of legal aid services, and weak enforcement of advocates’ pro bono obligations often prevent vulnerable individuals from securing adequate legal representation. These barriers undermine equality before the law and weaken the practical realization of fair trial guarantees. Pro bono legal aid is therefore crucial to ensure marginalized groups can participate meaningfully in civil proceedings, obtain formal and substantive justice, and reduce structural inequities. This study also connects pro bono practice to the Sustainable Development Goals, particularly SDG 16 (Peace, Justice, and Strong Institutions) and SDG 10 (Reduced Inequalities). Using a normative juridical approach with statute and comparative methods, this research examines Indonesian laws and regulations on pro bono legal aid and civil litigation. It also draws lessons from selected jurisdictions (United States, United Kingdom, Australia, China, Germany, and Canada) to identify institutional designs, accountability mechanisms, and best practices that can strengthen the implementation of pro bono services in Indonesia. Findings show that while pro bono legal aid is legally recognized and mandated as a professional duty, its implementation remains inconsistent. Challenges include weak monitoring, narrow eligibility focused mainly on economic poverty, low public awareness, and uneven access across regions. Strengthening these aspects is essential to make pro bono a systemic component of civil justice, ensuring inclusive access to justice, reducing inequalities, and advancing both national and international commitments to fairness and human rights.